Effect of the Olive Oil Extraction Process on the Formation of Complex Pectin-Polyphenols and Their Antioxidant and Antiproliferative Activities - Alejandra Bermúdez-Oria; Elisa Rodríguez-Juan; Guillermo Rodríguez-Gutiérrez; África Fernández-Prior; Juan Fernández-Bolaños (MDPI AG, 2021)
The aim of this research was to investigate the interaction of phenols and pectic polysaccharides during the olive oil extraction process. For this, pectin was extracted from fresh olive fruits and compared to the pectin isolated from the paste resulting from the extraction of the olive oil after milling with malaxation at 30 °C/30 min and subsequent centrifugation of the olive paste from the same lot of olive fruits in a system called ABENCOR (AB). The results indicate that these interactions were enhanced during the olive oil extraction process. In addition, the resulting AB extracts exhibited high antioxidant activity (ORAC) and strong antiproliferative activity in vitro against colon carcinoma Caco-2 cell lines compared to olive fruit extracts. The polyphenols associated mainly with the acidic pectin substance, with a higher content in AB extracts, seem to be responsible for these activities, and appear to maintain their activities in part after complexation. However, even in olive fruit extracts with smaller amounts of phenols in their compositions, pectic polysaccharides may also be involved in antioxidant and antiproliferative activities.